A microengineered collagen scaffold for generating a polarized crypt-villus architecture of human small intestinal epithelium. (June 2017) - Wang, Yuli; Gunasekara, Dulan B.; Reed, Mark I.; DiSalvo, Matthew; Bultman, Scott J.; Sims, Christopher E.; Magness, Scott T.; Allbritton, Nancy L.
Abstract: The human small intestinal epithelium possesses a distinct crypt-villus architecture and tissue polarity in which proliferative cells reside inside crypts while differentiated cells are localized to the villi. Indirect evidence has shown that the processes of differentiation and migration are driven in part by biochemical gradients of factors that specify the polarity of these cellular compartments; however, direct evidence for gradient-driven patterning of this in vivo architecture has been hampered by limitations of the in vitro systems available. Enteroid cultures are a powerful in vitro system; nevertheless, these spheroidal structures fail to replicate the architecture and lineage compartmentalization found in vivo, and are not easily subjected to gradients of growth factors. In the current work, we report the development of a micropatterned collagen scaffold with suitable extracellular matrix and stiffness to generate an in vitro self-renewing human small intestinal epithelium that replicates key features of the in vivo small intestine: a crypt-villus architecture with appropriate cell-lineage compartmentalization and an open and accessible luminal surface. Chemical gradients applied to the crypt-villus axis promoted the creation of a stem/progenitor-cell zone and supported cell migration along the crypt-villus axis. This new approach combining microengineered scaffolds, biophysical cues and chemical gradients to control the intestinal epithelium ex vivo can serve as a physiologically relevant mimic of the human small intestinal epithelium, and is broadly applicable to model other tissues that rely on gradients for physiological function. Graphical abstract: